2020
DOI: 10.1063/5.0031150
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sneezing on the flow around a face shield

Abstract: A flow analysis around a face shield was performed to examine the risk of virus infection when a medical worker wearing a face shield is exposed to a patient’s sneeze from the front. We ensured a space between the shield surface and the face of the human model to imitate the most popularly used face shields. In the present simulation, a large eddy simulation was conducted to simulate the vortex structure generated by the sneezing flow near the face shield. It was confirmed that the airflow in the space between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
14
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 22 publications
1
14
1
Order By: Relevance
“…They found that aerosols directed toward a shield-wearing person form ring-shaped vortices that reach the shield's top and bottom edges and form a high-velocity entrainment flow, quickly reaching the areas behind the shield. 35 In contrast to these data, our study results support the protective effect of face shields against contamination via aerosol as well as via spatter. As a third finding, in the experimental setup of our study, surgical masks and N95 (FFP2) or FFP3 respirators were equally effective in protecting the operator; even in a critical environment such as the aerosol-generating dental setting, the viral loads were below the detection limit when wearing both a surgical mask and a respirator.…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…They found that aerosols directed toward a shield-wearing person form ring-shaped vortices that reach the shield's top and bottom edges and form a high-velocity entrainment flow, quickly reaching the areas behind the shield. 35 In contrast to these data, our study results support the protective effect of face shields against contamination via aerosol as well as via spatter. As a third finding, in the experimental setup of our study, surgical masks and N95 (FFP2) or FFP3 respirators were equally effective in protecting the operator; even in a critical environment such as the aerosol-generating dental setting, the viral loads were below the detection limit when wearing both a surgical mask and a respirator.…”
Section: Discussioncontrasting
confidence: 72%
“…In the dental practice, especially during the COVID-19 pandemic, face shields are highly recommended when aerosol-generating procedures are performed. 7,14,15 However, limited data are available on the efficacy of face shields in blocking contamination via splashes and spatters, 15 and the authors of only 1 study indirectly evaluated their efficacy in reducing aerosol diffusion; Akagi and coworkers 35 performed a computational flow simulation that highlighted the relatively low efficacy of a face shield in protecting against aerosols. They found that aerosols directed toward a shield-wearing person form ring-shaped vortices that reach the shield's top and bottom edges and form a high-velocity entrainment flow, quickly reaching the areas behind the shield.…”
Section: Discussionmentioning
confidence: 99%
“…In the recent past, scientists have proposed various mitigation measures, 1–14 explained virus survival, 15–21 disinfecting strategies for surfaces, and protective measures efficacy. 22–29 Social distancing guidelines have also been proposed considering extreme events like coughing and sneezing. 30–33 For the general public, the policymakers have framed guidelines to curb the spread of COVID-19; this mainly includes a face mask, 34 social distancing, 35 and frequent handwash.…”
Section: Introductionmentioning
confidence: 99%
“…Arumuru et al [17] also agrees with Salimnia et al [18], arguing that the combination of the two masks is not feasible. In contrast, the computational model by Akagi et al [19] investigated the protection offered by face shields, concluding that this type of mask is not a good protection tool, as 4.4% of the droplets exhaled into the environment enter the gap between the human and the face shield. Wendling et al [20] carried out an experimental work to compare the barrier performance of face masks and face shields.…”
Section: Introductionmentioning
confidence: 99%